Business Environments for the Formation of Closed Loop Supply Chains - Odeh, Yasmeen (2008)
Closed loop supply chains (CLSCs) refer to supply chains where products or materials re-enter the production or distribution stream at some point during their lifecycles forming closed cycles. CLSCs have gained more importance in recent years due to the emergence of environmental legislation, and company recognition of economic benefits associated with value recovery from used goods. This study considers factors that play an important role in the establishment of CLSCs. Facilitators and obstacles encountered in forming closed loops are extracted from published cases. Another approach utilised in this study is the application of an existing supply chain paradigm that relates product type to supply chain characteristics in a reverse flow context. Some facilitating factors have been found to apply to most return types, such as designing modular components and standardised parts, establishing designated central returns facilities, and using information exchange and tracking technologies. However, the analysis conducted in this study suggests that certain factors have more influence on specific types of returns. Short life cycle products require responsive disposition and processing, enabled by systems that identify disposition alternatives, products that are designed for disassembly, and standardised grading and sorting systems. The same factors facilitate the recovery of less innovative factors such as photocopiers, although the time constraint is not as significant as in short life cycle products. The study also shows that efficient supply chains are required to accommodate to functional products (e.g. refillable containers, fast moving consumer goods), end of life products, material flows in industrial ecosystems, and repair parts of long life cycle products such as cars and jet engines. Facilitating factors for the formation of efficient CLSCs were found to be primarily cost-reduction related. They include establishing strong relationships with suppliers to maintain a stable supply, and with competitors to achieve higher economies of scale. Other factors include governmental support, physical proximity of supply chain partners, and the provision of enough incentives for them to engage in closed loop activities.